New taxa of foliicolous hyphomycetes - Cercospora, Corynespora and Phaeotrichoconis from North-eastern U.P., India - V.K. PAL, P.P. UPADHYAYA and D.K. AGRAWAL, RAGHVENDRA SINGH, SHAMBHU KUMAR, (Indian Phytopathology, 2007)
Three interesting foliicolous hyphomycetous species viz. Cercospora chrozophorina R. Singh et al. sp. nov.; Corynespora longissima R. Singh et al. sp. novoand Phaeotrichoconis distoseptata R. Singh et al. sp. nov.; parasitizing on the living leaves of Chrozophora rottleri (Euphorbiaceae), Fermiana colorata (Sterculiaceae) and Achyranthes aspera var. rubrofusca (Amaranthaceae) respectively, are described and illustrated. The specimens were collected from North-eastern Terai Belt of U.P. and deposited in H.C.1.0.,New Delhi and their corresponding isotypes have been retained in the departmental herbarium for further references. Morphotaxonomic determination being done on comparison with allied taxa in question and current literature.